Evaluation on the educational program of SMKTI in the city of Bandar Lampung - - Sumarno (JOURNAL OF EDUCATION, 2009)
This study aims to describe the educational program at Sekolah Menengah Kejuruan Teknologi dan Industri (SMKTI) in the city of Bandar Lampung, in terms of (1) program effectiveness, (2) program quality, and (3) gaps between SMKTI students employability skills and industrial demand the first time they work. The evaluation model employed was a combination between the model of context, input, process, output, and outcome (CIPOO) and the Provus gap model. The research subjects were SMKTI students registered in the academic year 2004/2005 and employees who were SMKTI graduates. The data collecting instruments were questionnaires. The data were analyzed using MANOVA and ANCOVA. The research findings indicate that (1) from the number of classes demanded and supplied and the attainment effect, the SMKTI educational program is ineffective and the indicator of future workforce market, the SMKTI educational program is ineffective, (2) the quality of SMKTI educational program is good in developing technological skills and personal management skills but not good in developing fundamental skills and teamwork skills, and (3) the SMKTI educational program is able to equip its students with the employability skills required the first time they work.